Analysis of Application of E-Tax Invoice in Improving Compliance with PP23 Tax Report 2018 (Case Study at CV Pusaka Utama) - Elsa Mayori; Siti Nuur Halimah (Budapest International Research and Critics University, 2022)
To be able to do tax reporting properly, good data collection is needed, including neatly and professionally in order to avoid tax reporting errors in the online tax system. In CV Pusaka Utama, data collection is still not carried out, both neat and professional. This study aims to analyze the Application of E-Tax Invoices in Improving Compliance with PP23 Tax Reporting in 2018 with a Case Study at CV Pusaka Utama. The method used in this study is a qualitative method described descriptively. Primary data comes from observation and documentation, while secondary data comes from literature review. The results show that the electronic tax invoice system, or the creation of electronic tax invoices, is intended not only to make it easier for PKP to report taxes, but also to avoid potential fraud when reporting taxes to be collected. In addition, good, neat and professional data collection is needed in order to be able to report correctly and avoid arrears or tax bills due to errors in reporting.